2020
DOI: 10.1177/0960327120934533
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite induces dysfunction of regulatory T cells through acetylation control of the Foxp3 promoter

Abstract: Arsenic is known to cause damage to the body’s immune system by inducing epigenetic changes. However, the molecular mechanism of this damage remains elusive. Here, we report that arsenic disrupts the morphology of lymphocytes, decreases cell viability, and results in abnormal proportions of T lymphocyte subsets. Moreover, our results revealed that arsenic can reduce global acetylation of histone H4 at K16 (H4K16 ac) in lymphocytes via decreasing the level of males absent on the first but upregulates mRNA and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…As for the upstream of MALAT, or the molecular basis of enhanced expression of MALAT1, we found that it can be attributed to the increased acetylation level of the transcription factor foxo1 under the administration of ATO or hypoxia. It has been previously reported that arsenic can remarkably promote histone acetylation [23][24][25] through inhibiting the enzyme activity of the deacetylase HDAC [23] or RNA epigenetics [25], and so on. Therefore, ATO may enhance the acetylation level of foxo1 through the above pathways.…”
Section: Discussionmentioning
confidence: 99%
“…As for the upstream of MALAT, or the molecular basis of enhanced expression of MALAT1, we found that it can be attributed to the increased acetylation level of the transcription factor foxo1 under the administration of ATO or hypoxia. It has been previously reported that arsenic can remarkably promote histone acetylation [23][24][25] through inhibiting the enzyme activity of the deacetylase HDAC [23] or RNA epigenetics [25], and so on. Therefore, ATO may enhance the acetylation level of foxo1 through the above pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lead treatment also significantly inhibited the activities of SOD, GPX, and CAT and increased the accumulation of nitric oxide (NO) and MDA to induce oxidative stress and activate MAPK/NF-ĸB signal pathway to cause splenic necrosis [ 102 ]. Arsenic can disrupt lymphocyte morphology, reduce cell viability, cause abnormal proportions of T lymphocyte subsets, and induce regulatory T cell (Tregs) dysfunction to cause immune damage [ 103 ]. Liu et al found that chickens exposed to arsenic showed a reduced IFN-γ/IL-4 ratio and an increased IL-17 level, which indicated an imbalanced immune response in vivo [ 104 ].…”
Section: Major Toxicity Mechanisms Induced By Mycotoxins and Heavy Me...mentioning
confidence: 99%